A Self Directed Adherence Management Program for Patients' with Heart Failure Completing Combined Aerobic and Resistance Exercise Training - Duncan, Kathleen (2009)
This study measured the impact of the Exercise Adherence Management Program (EAMP) provided to 20 patients with heart failure (HF) who participated in a combined resistance and aerobic exercise training program during two, 12 week phases. The EAMP included strategies designed to support exercise self-efficacy and adherence. Results indicate an improvement in exercise self-efficacy occurred during the study period while exercise adherence declined during the unsupervised phase. The highest rated adherence strategy for helpfulness and self-efficacy was group sessions. The study supports the use of adherence strategies based on self-efficacy in exercise programs for patients with HF.